Determinants of Attitude towards Supply Chain Finance Among Malaysian Manufacturing Companies: A Preliminary Investigation - Mohamad Aznillah Bin Ahmad; Jaafar Bin Pyeman; Norli Binti Ali; Norsariah Binti Abdul Rahman (International Journal of Supply Chain Management, 2018)
Supply chain finance can be regarded as a new way to support the competitiveness and resilience of companys financial performance since the financial crises in 2008. Despite many benefits that it can offer, the adoption rate was still very low especially in developing countries. In Malaysia, the lower adoption rate is witnessed by low penetration of supply chain finance among manufacturing industry players. Business must not only focus on conventional way of financing their projects but it is essentially finance the projects with less cost possible. However, this has not been met. The purpose of this paper is to examine the feasibility of the survey instrument in determining factors that influence the attitude towards supply chain finance among the manufacturing companies. A survey questionnaire is distributed to 40 manufacturing companies based on Federation of Malaysian Manufacturers 2017 directory books using random sampling technique as the preliminary investigation. The research findings justify further refinement and show that the survey instrument is appropriate in a wider study of a representative sample of the manufacturing industry.